Diseño e implementación de una estación de carga con sistema fotovoltaico para el campus universitario en cafetería de la Universidad Antonio Nariño sede Neiva-Buganviles (2024)
At the Antonio Nariño University of the Neiva-Buganviles campus, the cafeteria currently lacks a space where students can work and charge their electronic devices at the same time, however in said cafeteria they do not have access to the institutional internet. This situation makes it impossible for students to interact correctly with the virtual material that the university has available for all subjects. The thesis project focuses on the design and implementation proposal of a charging station with a photovoltaic system for the university campus in the cafeteria of the Antonio Nariño University, Neiva-Buganviles campus. The charging station with a photovoltaic system will allow students to have access to virtual material while they charge their electronic devices and can chat in the cafeteria, which allows the integration of an outdoor environment with the basic amenities offered by the library, with the with the support of the university, a point with a Wi-Fi network will be established that will be powered by the same photovoltaic system. Once the design and implementation of the charging station with photovoltaic system has been carried out, the use of students and teachers will allow the campus to not only be used for student integration but also for feedback activities that allow the development of future engineers, dentists, nurses among other careers that the Buganviles headquarters has. The SSFV will have 2 110V outlets and 4 USB ports to charge electronic devices, it also has reading lights and two seats that allow a maximum capacity of 4 students, the installed load of the SSFV is 808 Wh, which is made up of by, a 1500W peak 24V hybrid charger inverter, two 100Ah 12V batteries and two 500V peak panels which are mounted on a metal structure with an inclination of 13°.